A novel circular RNA circ_0020647 promotes ETEC-induced IPEC-J2 cell pyroptosis via the ssc-miR-185/BRD4 axis - Zhu, Kaiqing; Liu, Puyu; Liu, Kangping; Cui, Yanan; Jiang, Pengxin; Wang, Xutao; Chen, Ning; Cui, Jiamei; Hou, Zijuan; Li, Jianguo; Fan, Jinghui; Zuo, Yuzhu; et al. (Frontiers in Veterinary Science, 2025)
IntroductionEnterotoxigenic E. coli (ETEC) is a major pathogen causing piglet diarrhea. This study aimed to investigate the mechanism of porcine circular RNAs (circRNAs) in regulating intestinal immunity during ETEC infection.MethodsThe circRNA expression profiles were obtained in ETEC-infected and uninfected IPEC-J2 cells via RNA-sequencing. The stable covalently closed structure of circRNAs was validated using qRT-PCR and RNase R digestion methods. The potential circRNA/miRNA/mRNA interactions were analyzed using Miranda software, dual-luciferase reporter assay, knockdown and over-expression of the target gene or RNA. The expression of pyroptosis-related factors was assessed by qRT-PCR and Western blot. Flow cytometry was utilized to quantify pyroptotic cells, and transmission electron microscopy was used to observe cellular morphology.ResultsIn this study, a total of 328 differentially expressed circRNAs were identified in ETEC-infected versus uninfected IPEC-J2 cells, among which a novel circRNA named circ_0020647 was significantly upregulated post-infection. Circ_0020647, encoded by an intergenic sequence, forms a covalently closed loop structure. We demonstrated that circ_0020647 acts as a molecular sponge for miRNA ssc-mir-185 through direct binding, which in turn targets BRD4 mRNA. Following ETEC infection, circ_0020647 promoted pyroptosis in IPEC-J2 cells by increasing the expression of NLRP3, GSDMD, and caspase-1. Additionally, circ_0020647 was involved in ETEC-induced cell injury, characterized by LDH efflux, IL-1β and IL-18 secretion, formation of membrane pores, and mitochondrial abnormalities. We revealed that the role of circ_0020647 in regulating pyroptosis was mediated by the ssc-mir-185/BRD4 axis.ConclusionOur study constructed a novel circ_0020647/ssc-mir-185/BRD4 network that played an important role in the pyroptosis of IPEC-J2 cells induced by ETEC infection. Our findings imply that the circRNA/miRNA/mRNA network may be a novel biomarker and a potential therapeutic target for diarrhea in piglets caused by ETEC.